"Comprehensive Care" Concept in Nursing: Systematic Review - Renghea, Alina; Cuevas-Budhart, Miguel Angel; Yébenes-Revuelto, Hugo; Gómez del Pulgar, Mercedes; Iglesias-López, María Teresa (Investigación y Educación en Enfermería, 2023)
Introduction. Integrated health care is a concept widely used in the planning and organisation of nursing care. It is a highly topical concept, but at the same time it is deeply rooted in the theory and models of Nursing right from its inception as a science. There is no clear, agreed definition that describes it. Objective. To systematise the knowledge available on the concept of "comprehensive care" in Nursing from the point of view of nursing care, its domains and characteristics. Methods. A literature search has been carried out in several languages (Spanish, Portuguese, English and Romanian) in the databases Web of Science, Scopus, Medline, PubMed, Cochrane and Dialnet, covering the period between 2013 and 2019. The search terms used were: comprehensive health care, health and nursing. Prospero register 170327. Results. Sixteen documents were identified, which grouped 8 countries, mainly Brazil, being the country with the highest output on this context– 10 documents were found within the qualitative paradigm and 6 quantitative ones. The concept "Comprehensive" ; is commonly used to refer to comprehensive nursing care techniques, protocols, programmes and plans, covering care in all aspects of the individual as a complement to or independent of the clinical needs arising from health care. Conclusion. The definition of features pertaining to the concept "Comprehensive Care" ; encourages the use and standardisation of nursing care plans, improving patient follow-up, the detection of new risk factors, complications and new health problems not related to the reason for admission. This increases the capacity for prevention and improves the patient’s quality of life, and their primary and/or family caregivers, which translates into lower costs in the health system.